Reduction in Hypertension and Related Lipid Profile Parameters after Exercise in Females - Mushtaq, Rehana; Khan, Zahida Tasawar (Pakistan Journal of Nutrition, 2010)
The effect of exercise on BMI and plasma lipid profile has been investigated in hypertensive females of four ethnic groups of Baloch (B), Pathan (P), Hazara (H) and Punjabi (PU). A total of 32 females, i.e. 8 from each group as control and another batch of 32 females’ in similar distribution followed prescribed exercise protocol for ten weeks. After the trial fasting blood samples were collected from controlled group and exercised subjects. Exercise manifested significant decrement in Systolic Blood Pressure (SBP) in P, H and PU groups and of Diastolic Blood Pressure (DBP) in all the ethnic sub-populations. Marked and significant decrease of total cholesterol in all the ethnic groups was observed and the lowering of LDL cholesterol was also found in most except Pathan sub-population. Striking and significant rise of HDL of the exercising females was observed in all ethnic sub-populations. Triglyceride levels were considerably and significantly lowered in B, P, and H subjects. The beneficial effects of exercise on blood pressure and plasma lipids in female hypertensive subjects have been clearly demonstrated.